Advanced Liquid Electrolytes for Rechargeable Li Metal Batteries. (6th April 2020) - Jie, Yulin; Ren, Xiaodi; Cao, Ruiguo; Cai, Wenbin; Jiao, Shuhong
Abstract: Rechargeable lithium metal batteries (LMBs) have attracted wide attention for future electric vehicles and next‐generation energy storage because of their exceptionally high specific energy density. Recently, the development of electrode materials for LMBs has been extensively discussed and reviewed in the literature, but there have been very few reports that systematically review the status and progress of electrolytes for such applications. Actually, the viability of practical LMBs critically depends on the development of suitable liquid electrolytes due to the high reactivity of Li metals toward most solvents. This paper provides a systematic summary of the background and recent advances of the electrolytes for LMBs with an emphasis on the thermodynamic and kinetic stabilities at the interfaces. In addition, the emerging advanced characterization techniques for understanding the electrolyte–electrode interfaces are surveyed. Finally, a perspective for future directions is provided. Abstract : Nonaqueous electrolytes that realize high‐performance Li metal batteries are highly desirable. This review offers a brief overview of the development of nonaqueous electrolytes for rechargeable Li metal batteries, with attention concentrated on recent advances. In addition, understandings the electrode–electrolyte interface through emerging advanced characterization techniques is explored.